Caracterización del Sistema de Tenencia, Morfometría, Perfil Hematológico y Bioquímico del Asno Criollo Ecuatoriano en la Provincia de Cotopaxi. - Moya Enríquez, Dayana Paola (2019)
The characterization of the creole donkey is a fundamental tool for its conservation and sustainable use. The present work main goal was to characterize the tenure system, morphometry, hematological and biochemical profile of the Ecuadorian creole donkey in Cotopaxi province, as bases for its conservation and genetic improvement. The tenure system and its morphological structure were evaluated. A survey was applied to 100 donkey owners in cantons as Pangua, La Maná and Sigchos of the province of Cotopaxi. 16 body measurements were made, which were used for the definition of morphological indices in the 100 animals, the morphometric characteristics were defined by a zoomometric stick. There is poor information about this species, making it difficult to manage them, which puts the conservation of this zoogenetic resource at risk. It was evaluated that Pearson correlation exist, with the morphometric values obtained from the donkeys of Cotopaxi province, with other donkeys. Obtaining as result that the zoometrics indixes classified the creole donkey as longilineum and dolichocephalic. In certain morphological variables, a sexual dimorphism prevailed towards males. Also, blood samples were taken from 60 animals, classified according to sex; 38 males and 22 females, and age in the range (young <5 years old and adults >5 years old). For the blood sampling, the automated Neubauer quantification method was used. For the biochemical profile the colorimetric and enzymatic method was used. Variables were evaluated (Hematocrit, Hemoglobin, Erythrocytes, Mean Corpuscular Volume, Mean Corpuscular Hemoglobin, Mean Corpuscular Hemoglobin Concentration, Platelets, Leukocytes, Neutrophils, Lymphocytes, Total Proteins, Aspartate Aninotransferase, Alanine Aminotransferase, Alkaline Phosphatase, Alkaline Dehydrogenase, Creatine Kinase , Calcium, Phosphorus and Potassium). The statistical analysis included (ANOVA) with basic measures, arithmetic mean (Mean), standard deviation (Standard Deviation) and the InfoStat program was used through (ADEVA) establishing the Turkey test with a confidence level of 95%. The results showed average values for the race of Hematocrit (37,43 %), Hemoglobin (11,74 g/dL), Erythrocytes (5,98×106 /µL), Average levels of Leukocytes (9,72×103 /µL) and Neutrophils (3,76×103 /µL). The biochemical profile showed values of Glucose (4,49 mmol/ L) and Urea (4,88 mmol/ L). It was evaluated that the variables under study do not show differences between sexes or age groups with the exception of Aspartate Aminotransferase and Alanine Aminotransferase.